Development of Web Applications Using Google Technology - Nayak, Vaibhavi; Vinuta V, Naik; Vijaykumar, AS (International Journal of Computer Sciences and Engineering, 2025)
This paper describes some metrics to consider for web application development with frameworks like Google Web Toolkit and Google App Engine, technologies with a particular mode of operation and with some restrictions that affect the design and the functionality of these applications, but also offer great benefits such as improved user interface, better usability, improved performance, greater scalability and as the ability to use certain services, which allow application interoperability with different systems.